Single-antenna super-resolution positioning with nonseparable toroidal pulses - Ren Wang; Pan-Yi Bao; Xiaoyu Feng; Junpu Wu; Bing-Zhong Wang; Yijie Shen (Communications Physics)
Abstract The fundamental principle of satellite/node-based positioning involves triangulating the receiver’s coordinates through the intersection of spatial distances. Advancements in hybrid wireless networks have yielded high-precision positioning at decimeter-level (wavelength-level), approaching the resolution limits in free space. Here we present a 3D super-resolution positioning paradigm in free space by utilizing a kind of topologically structured pulses, toroidal electromagnetic pulses. We demonstrate that the space-time nonseparability and skyrmion topology inherent in toroidal pulses can be harnessed to achieve freespace microwave 3D positioning with super-resolution accuracy, reaching the centimeter level, using a single emitting antenna. This work opens up avenues for exploring the potential applications of topological electromagnetic pulses including but not limited to positioning, imaging and sensing technologies.